Comparative analysis of creative problem solving tasks across age groups using modular cube robotics - Anik, Mehedi Hasan; Romero, Margarida (Frontiers in Robotics and AI, 2024)
Creative Problem Solving (CPS) is an important competency when using digital artifacts for educational purposes. Using a dual-process approach, this study examines the divergent thinking scores (fluidity, flexibility, and originality) and problem-solving speed in CPS of different age groups. Participants engaged in CreaCube CPS tasks with educational robotics for two consecutive instances, with performance analyzed to explore the influence of prior experience and creative intentions. In the first instance, infants and children demonstrated greater originality compared to seniors, solving problems quickly but with less originality. In the second instance, teens, young adults, and seniors showed enhanced originality. The results highlight trends influenced by prior experience and creative intentions, emphasizing the need for customized instructions with modular robotics to improve CPS across the lifespan.